Effect of Chinese herbal medicine (CHM) as an adjunctive therapy in distinct stages of patients with COVID-19: A systematic review and meta-analysis - Jin-Min Gu; Shu-Nan Zhang; Si-Yao Xiao; Ming-Yue Jia; Jian-Feng Tu; Gui-Ling Han (PLoS ONE, 2025)
Background The pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory disease coronavirus 2 (SARS-CoV-2), has led to millions of infected cases and deaths worldwide. Clinical practice and clinical trials in China suggested that integrated Chinese herbal medicine (CHM) and conventional Western monotherapy (ICW) have achieved significant clinical effectiveness in treating COVID-19 patients. Objectives This article aims to systematically evaluate the effects of ICW in treating patients at distinct stages of COVID-19. The most frequently used components of the CHM formulas have been summarized to define the most promising drug candidates. Methods In this meta-analysis, seven databases up to May 20, 2024, were systematically searched to collect relevant randomized controlled trials (RCTs) and cohort studies (CSs). Difference in mean (MD) or ratio risk (RR) with 95% confidence interval (CI) was utilized for data processing analysis. Results A total of 46 studies, consisting of 24 RCTs and 22 CSs, and 10492 patients were included. ICW group showed significant improvement over the conventional Western monotherapy (CWM) group at all stages of COVID-19 patients. ICW therapy was effective in improving recovery rate of chest CT (RR = 1.21, 95%CI [1.13,1.29]), shortening negativity time of nucleic acid (MD = -2.14,95% CI [-3.70, -0.58]), suppressing the transition of mild/moderate patients into severe conditions (RR = 0.45, 95% CI [0.33,0.62]), and reducing mortality (RR = 0.45, 95% CI [0.37,0.55]) for severe/critical COVID-19. Furthermore, compared with severe/critical patients, mild/moderate COVID-19 patients proved more effective after being treated with ICW therapy. They had a higher recovery rate of chest CT manifestations (75.4% vs. 69.1%), shorter negativity time of nucleic acid (9.21 d vs. 14.89 d), reduced time to clinical symptom reduction (3.85d vs. 11d) and shortened days of hospital stays (15.9d vs 19.1d). As for inflammatory markers analysis, ICW regimens decreased the level of lymphocytes in mild/moderate and severe/critical patients (MD = -0.15, 95% CI [-0.18, -0.13]), but no statistical difference was observed in white blood cell count and neutrophils count (MD = 0.02, 95% CI [-0.14, -0.18]; MD = 0.22,95% CI [-0.7, 1.15], respectively). A different tendency was found in the C-reactive protein level, which significantly decreased at the early stage of COVID-19 in the ICW group (MD = 2.56, 95%CI [1.28,3.83]). Conclusion This meta-analysis demonstrates the significant superiority of ICW over single western monotherapy in improving clinical efficacy at distinct stages of Chinese COVID-19 patients. Subgroup analysis further showed that the earlier intervention of CHM may contribute to a better therapeutic effect. Trial registration PROSPERO ID: CRD42023401200.